Overview Of Home Ownership Law For Foreigners In The Context Of A Second Home In Indonesia - Apriansyah Abdullah N; Ridwan Nirwana; Anita Kamilah (Journal of Law and Border Protection, 2022)
The presence of Act Number 11 of 2020 concerning Job Creation provides several changes in several sectors including in the field of immigration which provides opportunities for foreigners to live in the framework of a second home with a residence permit period of 5 to 10 years and can be extended. The purpose of the study is to find out the conditions that must be met by foreigners to get a second home in Indonesia, and the legal basis for owning a second home from foreigners in Indonesia. The approach method used in normative juridical research is to provide legal certainty of land ownership for foreigners in the context of a second home while living in Indonesia. The results of the study are that foreigners who are permitted to obtain residential property in Indonesia are foreign nationals whose existence provides benefits, conducts business, works, or invests in Indonesia, and has a residence permit in accordance with the provisions. As for the dwellings that can be owned by foreigners in the context of a second house, they consist of landed houses which are on the right of use on state land or landed houses which are above the right of use on land with ownership rights or management rights, as well as flats located on above the right of use or right to build on land with management rights and above the right of use or right to build on land with ownership rights.